PENGARUH MEDIA BUKU HARIAN UNTUK MENINGKATKAN KETERAMPILAN MENULIS KARANGAN NARASI PADA SISWA KELAS V SEKOLAH DASAR - T. Aisyah Hasanah; Zariul Antosa; Eva Astuti Mulyani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Learning to write essays at school is considered unpleasant, tedious and even difficult for students. Students feel lazy to start writing, finding and developing ideas, especially developing creative ideas into a narrative essay. In addition, there are still many students who are less skilled in using writing rules in accordance with EYD (The Perfected Spelling). Therefore, this research aims to to determine the effect of diary media to improve narrative essay writing skills in grade V elementary school students. Type of the research was Pre-experiment and was design with One Group Pretest-Posttest. The subjects consists of 21 students grade V-B SDN 161 Pekanbaru. Hypothesis was tested by t-test. Based on the results obtained, the average student after being treated with learning using diary media (74,21) was higher than before being treated with learning using diary media (61,71), tcount with ttable is tcount > ttable (4,86 > 2,08596) with α=0,05 and dk=20. Based on the data from research result use tcount > ttable than the hypothesis Ha was accepted. It means there is an influence of diary media before and after being given treatment to improve the narrative essay writing skills of class V students at SDN 161 Pekanbaru.